2017
DOI: 10.1037/ser0000154
|View full text |Cite
|
Sign up to set email alerts
|

Using online interventions to deliver college student mental health resources: Evidence from randomized clinical trials.

Abstract: This study evaluated the efficacy of Internet-based stress management programs for college students. This approach is particularly fitting for students owing to a lack of mental health resources on campus and to high levels of Internet use among students. Because a history of interpersonal trauma (IPT) is associated with more distress and poorer academic performance, IPT history was assessed as a moderator of intervention efficacy. Students (N = 365) were randomly assigned to a mindfulness plus present control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 30 publications
2
47
1
6
Order By: Relevance
“…Several studies reported no follow-up measurements 60 62 63 136. Other studies used different intervals for the follow-up measurement after the intervention, ranging from two weeks up to six months 28 43 61 134 137. To focus on the longitudinal effects of our intervention, we examine participants again six months after randomisation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported no follow-up measurements 60 62 63 136. Other studies used different intervals for the follow-up measurement after the intervention, ranging from two weeks up to six months 28 43 61 134 137. To focus on the longitudinal effects of our intervention, we examine participants again six months after randomisation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Stallman and Kavanagh39 as well as Ebert et al 26 observed that university students show a high acceptance for and usability of online interventions. A growing body of research found that online interventions are helpful to improve mental health conditions 26 40–45. These effects can be enhanced by therapeutic guidance, meaning that participants receive additional support from an expert, either online or face-to-face while receiving the online intervention 6 46…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average effect size across four outcomes was small to moderate. Additional clinical trials have further established the efficacy of the perceived control intervention for reducing stress-related symptoms [16][17][18][19] . Increases in perceived present control also appeared to be the mechanism of change in symptoms 15,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these programs are also often effective. Web-based interventions have been useful in decreasing illicit substance use [ 4 ], smoking cessation [ 5 ], healthy weight management [ 6 ], and the promotion of mental health [ 7 ].…”
Section: Introductionmentioning
confidence: 99%